Effects of physical activity on anthropometric variables and functional capacity of patients with type 2 diabetes - Teixeira, Robson Bonoto; Lima, Luciana Moreira; Xavier, Yuri Lucas; Lade, Carlos Gabriel de; Lopes, Gabriela Fernandes; Reis, Hamilton Henrique Teixeira; Marins, João Carlos Bouzas (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Type 2 Diabetes Mellitus affects current society, and is associated with overweight and obesity. Physical exercise has been showing favorable results in the anthropometric parameters and in the gain of joint flexibility and body mobility in these individuals. Objective: The objective of this study was to analyze the interference of an exercise program in anthropometric measures, flexibility and body mobility in type 2 diabetics. Method: This is a longitudinal study, performed with 14 type 2 diabetic patients, with a mean age of 55± 9 years, both genders, separated in aerobic group (n=8) and resistance group (n=6). The body mass index, waist circumference, abdominal circumference, hip circumference, waist-hip ratio, fat percentage, limp-femoral flexibility and body mobility were assessed before and after a 10-week period of aerobic or resistance exercises with a weekly frequency of 3 days. Results: For the analysis of the results, it was applied the paired t test (pre x post exercise) and independent t test (aerobic group x resistance group) with significance level of 5%. No significant differences were found in the anthropometric variables in both groups after the 10-week period of supervised training. In relation to the body mobility test, we observed a significant difference in the total sample (p=0.02), in the aerobic group (p=0.02) and in the resistance group (p=0.04). The coxofemoral flexibility test showed significant improvement (p=0.02) in the total sample and clinical improvement in aerobic (p=0.12) and resistance (p=0.09) groups. Conclusion: Both aerobic and resistance training provided positive effects in the coxofemoral flexibility and body mobility tests. In contrast, there was no significant improvement in anthropometric variables after 10 weeks of physical exercise.